Diastereoselective synthesis of (A±)- epi-subincanadine C - Kalshetti, Manojkumar; N. P. Argade (ACS Omega, 2018)
Starting from indolylmaleimide, concise and efficient total synthesis of (±)-epi-subincanadine C was described via stereoselective Wittig olefination, base-induced selective mono-prenylation, regioselective Grignard reaction, diastereoselective Pictet–Spengler cyclization, regioselective oxidative carbon–carbon double-bond cleavage, one-pot reductions, and intramolecular cyclization pathway. An attempted synthesis of (±)-subincanadine C via diastereoselective Grignard addition to the α,β-unsaturated γ-lactam or diastereoselective reduction of a carbon–carbon double bond also resulted in yet another route to (±)-epi-subincanadine C.